Foucault's Docile Bodies Perspective: The Figure of Seniwati's Feminism in the Wido Documentary Film - Ajie, Purwoko; Habsari, Sri Kusumo; Ardianto, Deny Tri (Humanus, 2023)
Discussion of docile bodies has been absent in film analysis. Most research is attracted to study gender representation in which women are frequently underrepresented. Thus, this study aims to examine the documentary film of Wido, a female artist, through Michel Foucault's theory of docility. This research is attracted to Widowati's narration as a Javanese woman artist who must be able to manage between her profession as an artist and a housewife respectfully. The data are the narration and scenes of Wido as both a female artist and a housewife in the documentary movie “Wido”. All data obtained are analysed textually, applying Foucault's notion of docile bodies. The research argues that the representation of Wido challenges the notion of docile bodies. Despite Widowati still glorifying her domestic roles, the feminine prescription of which women should be responsible for domestic chores, she subsequently exchanges the domestic responsibility with her husband to work in public as an artist. She also acknowledges that she is the family's breadwinner without diminishing her husband's primary responsibility as the head of the family. The fluidity of gender roles she performs contradicts the notion of docile bodies in which women are always taught and supervised to glorify their femininity.